2020
DOI: 10.3390/cancers12020363
|View full text |Cite
|
Sign up to set email alerts
|

Integrin α7 and Extracellular Matrix Laminin 211 Interaction Promotes Proliferation of Acute Myeloid Leukemia Cells and Is Associated with Granulocytic Sarcoma

Abstract: Acute myeloid leukemia (AML) with granulocytic sarcoma (GS) is characterized by poor prognosis; however, its underlying mechanism is unclear. Bone marrow samples from 64 AML patients (9 with GS and 55 without GS) together with AML cell lines PL21, THP1, HL60, Kasumi-1, and KG-1 were used to elucidate the pathology of AML with GS. RNA-Seq analyses were performed on samples from seven AML patients with or without GS. Gene set enrichment analyses revealed significantly upregulated candidates on the cell surface o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 66 publications
2
10
0
Order By: Relevance
“…COL6A3 itself has previously been implicated in mediation of chemoresistance in breast cancer, with upregulation of collagen VI, the heterotrimer to which COL6A3 contributes, in breast cancers [40], and endotrophin, a soluble C-terminal domain cleaved from the COL6A3 protein, associated with cisplatin resistance in a mouse model [41]. ITGA7, which acts as a receptor for a number of laminins [42,43], has also recently been implicated in chemoresponse [44,45], although not in the context of breast cancer. A more surprising over-represented pathway was type II diabetes (with CACNA1C from our prioritized gene list).…”
Section: Discussionmentioning
confidence: 99%
“…COL6A3 itself has previously been implicated in mediation of chemoresistance in breast cancer, with upregulation of collagen VI, the heterotrimer to which COL6A3 contributes, in breast cancers [40], and endotrophin, a soluble C-terminal domain cleaved from the COL6A3 protein, associated with cisplatin resistance in a mouse model [41]. ITGA7, which acts as a receptor for a number of laminins [42,43], has also recently been implicated in chemoresponse [44,45], although not in the context of breast cancer. A more surprising over-represented pathway was type II diabetes (with CACNA1C from our prioritized gene list).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the RNAseq screen also identified the Itga7 gene, which encodes α7 integrin protein that dimerizes exclusively with β1 integrin. The integrin α7β1 is a receptor for laminins [49], with deletion of Itga7 in mice leading to muscular dystrophy-like phenotypes due to defective adhesion and signaling pathways in skeletal muscle cells [50]. Some Itga7-/-mice develop vascular pathologies including cranial hemorrhage, which has been attributed to loss of α7β1 functions in vascular smooth muscle cells [51].…”
Section: Discussionmentioning
confidence: 99%
“…Another study using antibodies targeting VLA-4 observed that blockade of VLA-4 in combination with CD3 redirection sensitized cytotoxicity [ 107 ]. Recently, a study investigated the role of integrin α7 in AML cells and found that the elevated expression of integrin α7 in AML activated ERK signal and impaired sensitivity to the stromal-induced drug resistance [ 108 , 109 ]. The selective pressure of cumulative cytotoxic therapies over time gradually contributes to the transformation from random genetic mutations to acquired resistance in these surviving cell subsets, eventually causing residual leukemic cell expansion and disease relapse.…”
Section: Role Of Interaction Between Bmm and Lscs In Environment-mediated Drug Resistance (Emdr)mentioning
confidence: 99%